Utilization of Thermoelectric Generators (TEG) to Convert Zinc Roof Heat into Electrical Energy - Dintje Pahrudin; Asri Arbie; Dewa Gede Eka Setiawan; Muhammad Yunus; Septiana Kurniasari; Irsan Irsan (BULETIN FISIKA, 2025)
The increasing need for electrical energy due to technological growth requires using sustainable alternative energy sources. One potential energy source is solar energy, which can be converted into electricity through a thermoelectric generator (TEG). This study aims to design an optimal TEG configuration in converting heat from zinc roofs into electricity and to analyze the effect of variations in the shape of zinc roofs on the electrical power generated. The method used is an experiment with variations in the type of zinc roof, e.g. plate, wave, and box, and the TEG circuit configuration, e.g series and parallel. Measurements were made on the temperature, voltage, current, and electrical power generated, both with and without supercapacitors as energy storage. The results showed that zinc plates with a parallel configuration produced the highest electrical power of 0.01372 W, compared to zinc boxes and wave zinc. The parallel configuration proved to be more efficient than the series configuration. In addition, using supercapacitors also increases the electrical power generated and allows for greater energy storage.